2017
DOI: 10.1007/s15010-017-1024-1
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the risk and disease burden of Clostridium difficile infection among patients with hospital-acquired pneumonia at a University Hospital in Central China

Abstract: PurposeHospital-acquired pneumonia (HAP) remains one of the major hospital-acquired infections in China. Antibiotic treatment of HAP may lead to subsequent Clostridium difficile infection (CDI). Baseline data on the occurrence of CDI among HAP patients in China are currently unavailable. This study examines the risk and disease burden of CDI among HAP hospitalized patients (HAP-CDI).MethodsWe conducted a prospective study among ICU patients with HAP and hospital-onset diarrhea from January 2014 to December 201… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
21
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 29 publications
(32 reference statements)
2
21
1
Order By: Relevance
“…A few isolates with low resistance or reduced susceptibility to vancomycin have been were reported in China [23–25]. All C. difficile isolates in this study showed resistance to clindamycin and cefoxitin, similar to clinical C. difficile in China and other countries [23, 24, 26, 27]. All C. difficile isolates in this study exhibited high susceptibility to tetracycline, consistent with clinical isolates in China [23].…”
Section: Discussionsupporting
confidence: 79%
“…A few isolates with low resistance or reduced susceptibility to vancomycin have been were reported in China [23–25]. All C. difficile isolates in this study showed resistance to clindamycin and cefoxitin, similar to clinical C. difficile in China and other countries [23, 24, 26, 27]. All C. difficile isolates in this study exhibited high susceptibility to tetracycline, consistent with clinical isolates in China [23].…”
Section: Discussionsupporting
confidence: 79%
“…This distribution is similar to previous studies in China which identified the following strains: ST54 (23%), ST35 (19.3%), ST37 (9.9%) ( Chen et al, 2014 ). Our previous study on CDI among patients with hospital-acquired pneumonia showed that the predominant types of C. difficile were ST54 (20%), ST37 (15.6%), and ST3 (9.4%) ( Li et al, 2017 ). Although the North American/European epidemic strain RT027/ST1 was not detected, ST201, a toxin A+B+ strain that also contains a gene for binary toxin and has been associated with severe diarrhea ( Li et al, 2015 ), was detected.…”
Section: Discussionmentioning
confidence: 99%
“…The number of bedridden patients increases with the increasing prevalence and incidence of diseases among older population (1). Staying in bed at hospital could cause many complications, and pneumonia is one of the most common complications.…”
Section: Introductionmentioning
confidence: 99%